MICROPROPAGATION OF GRAPEVINE (VITIS VINIFERA L.) CVS. RED GLOBE AND SUPERIOR - S., Osama .S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was conducted to develop a protocol for micropropagation of grapevine (Vitis vinifera L.) cultivars Red globe and Superior by investigating their response to three media Murashige and Skoog (MS), Chee and Pool (C2D), and Woody Plant Medium (WPM) during the establishment stage besides study the impact of four cytokinin types 6-benzylaminopurine (BA), 2-isopentyladenine (2iP), kinetin (Kin) and thidiazuron (TDZ) at various concentrations on the shoot multiplication as well as acclimatization of neoformed plantlets on several media. A completely randomized design (CRD) was used and data were analyzed by SASS 9.1. The results revealed that the WPM medium was optimum in terms of shoot length and leaf number (4.00 cm, 5.10) respectively. On the other side, Red globe gave the best results on both C2D and WPM media in average shoot length (4.38, 4.46 cm) and average leaf number (6.00, 5.42) respectively. In the multiplication stage and at 1 mgL-1, BA showed the longest shoot and leaf number (2.3, 6.67) respectively. While kin gave the maximum shoot length with a mean of 3.57 cm. Moreover, BA significantly at 1 mgL-1, 2iP at 2 mg L-1, Kin at 5 mgL-1 , and TDZ at 1 mgL-1 gave the highest values compared to other concentrations. Plantlets acclimatization results revealed that sterilized 1:1:1 (v:v) peatmoss+perlite+sand mix gave the highest survival rate (100.00%) and showed the best vegetative growth.